Boosting Motivation with 3D E-Modules: Discovery Learning for Vocational IT Students - Hermansyah, Winda Adelia; Patmanthara, Syaad; Soraya, Dila Umnia; Sutapa, Yohanes Gatot (Universitas Negeri Malang, 2023)
PISA (Program for International Student Assessment) scores over the past 20 years show that many Indonesian students are still unable to understand simple reading or basic concepts in certain subjects. Integrating technology with education is the main focus to eliminate the existing gap both in terms of recognition and utilization of the abilities of learners. Electronic modules (e-modules) are one of the alternatives that can be used to deepen understanding of the material and increase student motivation in learning. This research aims to develop a flipbook-based e-module equipped with 3D models containing discovery learning stages as an effort to increase the learning motivation of grade X students, especially in the subject of basics of computer network engineering and telecommunications elements of technological developments in the field of computer network engineering and telecommunications. Research and development conducted using the Hannafin and Peck model with stages including (1) needs analysis, (2) design, and (3) development and implementation where each stage is accompanied by evaluation and revision. This research resulted in a media validation test value of 95.50% or very feasible and the material expert validation test resulted in a value of 97.20% or very feasible. The product trial stage was carried out at SMK Negeri 8 Malang with the results of a small group trial of 89.93% or very feasible and a large group trial of 91.72% or very feasible. Measurement of student learning motivation obtained a gain score of 0.63 or a moderate increase category, from 72.99% in the high category to 90.10% in the very high category.